Pojęcie figury konceptualnej - Kudra, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The classical rhetoric knows the notion of the rhetoric figures – thoughts and words. The conceptual figure (the term “conceptual” includes both “notioning” and “linguification”) is determined from a different point of reference – i.e. from text conceptualisation perspective. In such an understanding of the conceptual figure is mainly connected with inventio, and less with dispositio and elocutio, it is a specific conceptual amalgamation (blend) and a hiperonim for various tropic conceptualisations. In text it includes both micro- and macro-conceptual strategies.